Secondary battery and preparation method thereof

By replacing the traditional separator with gel electrolyte membrane in lithium-ion batteries, the safety hazards and performance degradation of the separator during high temperature and circulation are solved, and excellent high-voltage cycling performance and extended cell cycle life are achieved.

CN119864500APending Publication Date: 2025-04-22ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411990023.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The separator of traditional lithium-ion batteries is prone to shrink and melt under high temperature conditions, and is prone to wrinkles during the battery cell cycle, affecting the safety and cycle life of the battery.

Method used

A gel electrolyte membrane is used to replace the traditional separator. By coating the gel electrolyte membrane made of photocuring resin, electrolyte, binder, photoinitiator and pore-forming agent on the positive and negative electrode sheets, ensuring that the electrolyte and the electrode sheet are closely linked.

Benefits of technology

It achieves excellent performance under high-voltage circulation conditions, reduces the risk of electrolyte breaking at corners, extends the cycle life of the battery cell, and improves interface stability and oxidation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223445920000021
    Figure BDA0005223445920000021
  • Figure BDA0005223445920000051
    Figure BDA0005223445920000051
  • Figure FDA0005223445900000011
    Figure FDA0005223445900000011
Patent Text Reader

Abstract

The invention discloses a secondary battery and a preparation method thereof. The secondary battery comprises a positive pole piece, a negative pole piece and an electrolyte, the electrolyte is arranged between the positive pole piece and the negative pole piece, and the electrolyte comprises a first gel electrolyte membrane and a second gel electrolyte membrane. The gel electrolyte membrane provided by the invention can replace a conventional diaphragm, and has excellent interface stability and cycle performance at the same time. The interface stability of the quasi-solid-state lithium ion battery can be improved by coating the negative electrode with a layer of gel electrolyte membrane, the oxidation resistance of a positive electrode interface can also be effectively improved by the inorganic filler contained in the gel electrolyte membrane on the positive electrode, and the high-voltage cycle performance of the quasi-solid-state lithium ion battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of secondary batteries, and specifically to a secondary battery and its preparation method. Background Technology

[0002] Lithium-ion batteries dominate the market due to their high energy density and long cycle life. With increasing global focus on sustainable development, the demand for lithium-ion batteries continues to grow, driving innovation and progress in related technologies. A lithium-ion battery mainly consists of a positive electrode, a negative electrode, a separator, an electrolyte, and outer packaging. The separator, as a crucial component preventing electron conduction between the positive and negative electrodes, directly affects the battery's safety, cycle life, and overall performance.

[0003] Traditional polyolefin separators are widely used due to their excellent mechanical strength and chemical stability, but they are prone to shrinkage and melting under high temperatures, posing certain safety hazards. Furthermore, during the winding and cyclic expansion of the battery cell, the separator is prone to wrinkling, which poses a serious risk to subsequent recycling. In addition, the high-energy-density cells currently fabricated using silicon-carbon anodes place higher demands on separator performance; the significant volume expansion and lithium dendrite growth present new challenges. Therefore, developing high-performance and safe separators is one of the current difficulties in the development of lithium-ion batteries.

[0004] Therefore, it is indeed necessary to develop a secondary battery whose electrolyte can replace the conventional separator while also having excellent high-voltage cycling performance. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a secondary battery whose electrolyte can replace conventional separators while also exhibiting excellent high-voltage cycling performance.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A secondary battery includes a positive electrode, a negative electrode, and an electrolyte; the electrolyte is disposed between the positive electrode and the negative electrode, and the electrolyte includes a first gel electrolyte membrane and a second gel electrolyte membrane.

[0008] Preferably, the first gel electrolyte membrane is disposed on the negative electrode sheet, and the second gel electrolyte membrane is disposed on the positive electrode sheet.

[0009] Preferably, the thickness of the second gel electrolyte membrane is greater than the thickness of the first gel electrolyte membrane.

[0010] Preferably, the thickness of the first gel electrolyte membrane is 3-6 μm, and the thickness of the second gel electrolyte membrane is 5-8 μm.

[0011] Preferably, the thickness ratio of the gel electrolyte membrane to the electrode sheet is 1:(10-50).

[0012] Preferably, the electrolyte comprises the following raw materials in parts by weight:

[0013]

[0014] Preferably, the photocurable resin is at least one selected from bisphenol A diethylene glycol epoxy resin, triethylene glycol diamine diphenylmethane epoxy resin, isophorone diisocyanate, dimethylsiloxane, and trimethylsiloxysilicate.

[0015] Preferably, the lithium salt is at least one selected from LiPF6, LiBOB, LiBF4, LiBOB, LiTFSI, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2.

[0016] Preferably, the organic solvent is at least one selected from dichloromethane, tetrahydrofuran, dimethylformamide, and dimethyl sulfoxide.

[0017] Preferably, the inorganic filler is at least one of Al2O3, ZrO2, La2O3 and TiO2; and / or, the particle size of the inorganic filler is 50-900 nm.

[0018] Preferably, the polymer is at least one selected from polyvinylidene fluoride, polyacrylate, polyimide, and polymethyl methacrylate;

[0019] And / or, the photoinitiator is at least one of diaryliodonium salt, phenylxyl ketone, 1-hydroxycyclohexylphenyl ketone, and dibenzoyl oxide.

[0020] Preferably, the pore-forming agent is at least one of a volatile organic compound and / or polyvinyl alcohol, polystyrene, and polyurethane;

[0021] And / or, the dispersant is at least one of sodium dodecyl sulfate, polyethylene glycol, polyacrylic acid, and (3-aminopropyl)triethoxysilane.

[0022] Furthermore, the present invention also provides a method for preparing a secondary battery, comprising the following steps:

[0023] Step S1: Add the negative electrode inorganic filler and dispersant to an organic solvent, disperse them evenly to obtain the first slurry, and add the positive electrode inorganic filler and dispersant to an organic solvent, disperse them evenly to obtain the second slurry.

[0024] Step S2: Add the photocurable resin, electrolyte, binder, photoinitiator and pore-forming agent to the first slurry, and disperse them evenly to obtain the first electrolyte slurry. Add the photocurable resin, electrolyte, binder, photoinitiator and pore-forming agent to the second slurry, and disperse them evenly to obtain the second electrolyte slurry.

[0025] Step S3: Coat the surface of the active material layer of the negative electrode sheet and the surface of the active material layer of the positive electrode sheet with the first electrolyte slurry and the second electrolyte slurry respectively, let stand, heat at 45-75℃ for 0.5-2h, and then place under ultraviolet light to cure for 0.1-1h, thereby obtaining the positive electrode sheet and the negative electrode sheet.

[0026] Step S4: Stack the positive electrode and negative electrode in sequence, with the electrolyte located between the positive and negative electrode to provide safety isolation. Wind the cells to obtain a bare cell, seal the top and side with an aluminum-plastic film, inject electrolyte and encapsulate to obtain the secondary battery.

[0027] In step S1, the weight ratio of the negative electrode inorganic filler to the positive electrode inorganic filler is 1:(2-5).

[0028] Compared to existing technologies, the advantages of this invention are as follows: the gel electrolyte membrane in this invention can replace conventional separators while possessing excellent high-voltage cycling performance. During battery cycling, lithium ions are released from the positive electrode and embedded in the negative electrode through a uniform gel electrolyte membrane formed by photocuring. At this time, there are no free electrons at the electrolyte interface on the negative electrode side, so free lithium ions will not deposit at the interface. Photocuring a layer of gel electrolyte membrane on the negative electrode interface can improve the interface stability of the quasi-solid-state lithium-ion battery. The inorganic filler contained in the gel electrolyte membrane on the positive electrode interface can also effectively improve the oxidation resistance of the positive electrode interface, further enhancing the interface stability of the quasi-solid-state lithium-ion battery. In particular, in the later stages of cell cycling, the expansion effect causes gaps between the cell electrodes and the traditional separator. This will cause the electrolyte to interrupt flow at the corners and lithium plating to occur, severely affecting the long-cycle performance of the cell. When using a gel electrolyte membrane to replace the traditional separator, its strong bonding with the electrodes allows the cell electrodes to adhere tightly to the electrolyte layer even during expansion. The electrolyte layer structure at the corners can extend the cycle life of the cell. Detailed Implementation

[0029] To make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] According to a first aspect of this application, this application provides a secondary battery, including a positive electrode, a negative electrode, and an electrolyte; the electrolyte is disposed between the positive electrode and the negative electrode, and the electrolyte includes a first gel electrolyte membrane and a second gel electrolyte membrane.

[0031] Under long-cycle conditions in battery cells, traditional separators provide good adhesion to the main body interface. However, at the cell corners, the expansion changes during charging and discharging cause gaps between the separator and the electrode, leading to electrolyte interruption and the risk of lithium plating. Compared to conventional separators, using a gel electrolyte membrane can enhance the adhesion between the electrolyte and the electrode, reducing the gap between them during expansion. Especially at the cell corners, the gel polymer electrolyte can tightly adhere to the electrode interface at the corner, providing a lithium-ion transport channel and thus reducing the risk of lithium plating at the corner.

[0032] In some embodiments, the first gel electrolyte membrane is disposed on the negative electrode plate, and the second gel electrolyte membrane is disposed on the positive electrode plate.

[0033] In some embodiments, the thickness of the second gel electrolyte membrane is greater than the thickness of the first gel electrolyte membrane. If the thickness of the second gel electrolyte membrane is too large, the lithium-ion migration path is too long, resulting in reduced cell cycle performance. If the thickness of the second gel electrolyte membrane is less than that of the first gel electrolyte membrane, the cell has poor oxidation resistance and the cell cycle degradation is faster.

[0034] In some embodiments, the thickness of the first gel electrolyte membrane is 3-6 μm, for example, it can be 3 μm, 4 μm, 5 μm or 6 μm; the thickness of the second gel electrolyte membrane is 5-8 μm, for example, it can be 5 μm, 6 μm, 7 μm or 8 μm.

[0035] In some embodiments, the ratio of the thickness of the gel electrolyte membrane to the thickness of the electrode is 1:(10-50), for example, it can be 1:10, 1:20, 1:30, 1:40, or 1:50.

[0036] In some embodiments, the electrolyte comprises the following raw materials in parts by weight:

[0037]

[0038] Among them, the photocurable resin provides a strong binding effect of molecular-level cross-linking network. Controlling its weight part to 10-25 parts can make the cured gel electrolyte membrane have both flexibility and mechanical strength. If the weight part is too large, the gel electrolyte membrane will become brittle, with poor flexibility and difficulty in adhering to the electrode.

[0039] When the weight percentage of the photocurable resin is too high, it will result in a dense cross-linked network and poor liquid storage effect. When the weight percentage of the binder is too low, it will result in increased electrolyte hardness, making it unable to adhere tightly to the electrode and peeling off during cycling. When the weight percentage of the binder is too high, it will result in low curing strength of the gel electrolyte membrane.

[0040] In some embodiments, the photocurable resin is at least one selected from bisphenol A diethylene glycol epoxy resin, triethylene glycol diamine diphenylmethane epoxy resin, isophorone diisocyanate, dimethylsiloxane, and trimethylsiloxysilicate. Preferably, it is bisphenol A diethylene glycol epoxy resin.

[0041] In some embodiments, the lithium salt is at least one of LiPF6, LiBOB, LiBF4, LiBOB, LiTFSI, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2.

[0042] In some embodiments, the organic solvent is at least one selected from dichloromethane, tetrahydrofuran, dimethylformamide, and dimethyl sulfoxide.

[0043] In some embodiments, the inorganic filler is at least one selected from Al2O3, ZrO2, La2O3, and TiO2, and / or the particle size of the inorganic filler is 50-900 nm, for example, it can be 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, or 900 nm. When the particle size of the inorganic filler is too small, it leads to increased costs; when the particle size of the inorganic filler is too large, it leads to a reduction in the surface area of ​​the filler particles in contact with the electrolyte, thus reducing the lithium-ion transfer rate.

[0044] In some embodiments, the polymer is at least one selected from polyvinylidene fluoride, polyacrylate, polyimide, and polymethyl methacrylate;

[0045] And / or, the photoinitiator is at least one of diaryliodonium salt, phenylxyl ketone, 1-hydroxycyclohexylphenyl ketone, and dibenzoyl oxide.

[0046] In some embodiments, the pore-forming agent is a volatile organic compound and / or at least one of polyvinyl alcohol, polystyrene, and polyurethane;

[0047] And / or, the dispersant is at least one of sodium dodecyl sulfate, polyethylene glycol, polyacrylic acid and (3-aminopropyl)triethoxysilane.

[0048] According to a second aspect of this application, this application provides a method for preparing a secondary battery, comprising the following steps:

[0049] Step S1: Add the negative electrode inorganic filler and dispersant to an organic solvent, disperse them evenly to obtain the first slurry, and add the positive electrode inorganic filler and dispersant to an organic solvent, disperse them evenly to obtain the second slurry.

[0050] Step S2: Add the photocurable resin, electrolyte, binder, photoinitiator and pore-forming agent to the first slurry, and disperse them evenly to obtain the first electrolyte slurry. Add the photocurable resin, electrolyte, binder, photoinitiator and pore-forming agent to the second slurry, and disperse them evenly to obtain the second electrolyte slurry.

[0051] Step S3: Coat the surface of the active material layer of the negative electrode sheet and the surface of the active material layer of the positive electrode sheet with the first electrolyte slurry and the second electrolyte slurry respectively, let stand, heat at 45-75℃ for 0.5-2h, and then place under ultraviolet light to cure for 0.1-1h, thereby obtaining the positive electrode sheet and the negative electrode sheet.

[0052] Step S4: Stack the positive electrode and negative electrode in sequence, with the electrolyte located between the positive and negative electrode to provide safety isolation. Wind the cells to obtain a bare cell, seal the top and side with an aluminum-plastic film, inject electrolyte and encapsulate to obtain the secondary battery.

[0053] In step S1, the weight ratio of the negative electrode inorganic filler to the positive electrode inorganic filler is 1:(2-5), for example, it can be 1:2, 1:3, 1:4 or 1:5.

[0054] The heating temperature can be 45℃, 50℃, 55℃, 60℃, 65℃, 70℃ or 75℃, the heating time can be 0.5h, 1h, 1.5h or 2h, and the curing time can be 0.1h, 0.5h, 0.8h or 1h.

[0055] When the heating temperature is too low, the solvent evaporation time will be too long. When the heating temperature is too high, the electrolyte will shrink too quickly and delaminate from the electrode. When the heating time is too short, organic solvent residue will remain. When the heating time is too long, the electrolyte surface will crack. When the curing time is too short, the electrolyte will not cure completely. When the curing time is too long, the curing efficiency will be too low.

[0056] In some embodiments, the positive electrode inorganic filler is selected from Li7La3Zr2O 12 Li4Ti5O 12 At least one of Al2O3, LiAlO2, ZrO2, SiO2, TiO2 and Li2B4O7.

[0057] In some embodiments, the inorganic filler for the negative electrode is selected from Al2O3, SiO2, ZrO2, TiO2, LiAlO2, Li4SiO4, Si3N4, Li3PO4, Li1+xAlxTi2-x(PO4)3, Li3N, BN, and Li4Ti5O. 12 At least one of TiB2 and TiB2.

[0058] The positive electrode includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The positive active material layer includes a positive active material, which may be, but is not limited to, a chemical formula such as Li. a Ni x Co y M z O 2-b N b (where 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from one or more combinations of Mn and Al, and N is selected from one or more combinations of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5 The positive electrode active material can be one or more combinations of O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, and TiS2. The positive electrode active material can also be modified. Methods for modifying the positive electrode active material are known to those skilled in the art. For example, coating, doping, and other methods can be used to modify the positive electrode active material. The materials used for modification can be one or more combinations of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, and W, including but not limited to. The positive electrode current collector is typically a structure or component that collects current. The positive electrode current collector can be any material suitable for use as a positive electrode current collector in lithium-ion batteries. For example, the positive electrode current collector can be, but is not limited to, metal foil, and more specifically, aluminum foil, among others.

[0059] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, which may be one or more of the following: graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate, or other metals that can form alloys with lithium. Specifically, the graphite may be selected from one or more of artificial graphite, natural graphite, and modified graphite; the silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; and the tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is typically a structure or component that collects current. The negative electrode current collector may be any material suitable for use as a negative electrode current collector in lithium-ion batteries, for example, it may be, but is not limited to, metal foil, and more specifically, copper foil.

[0060] The secondary battery also includes an electrolyte, which comprises an organic solvent, an electrolyte lithium salt, and additives. The electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in overcharge-resistant electrolytes; or it can be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; or it can be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include, but are not limited to, at least one of film-forming additives, conductive additives, flame-retardant additives, overcharge-resistant additives, additives for controlling the H2O and HF content in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0061] Example 1

[0062] Preparation of negative electrode:

[0063] Step S1: 97.7% graphite, 1.2% polystyrene-butadiene copolymer and 1.1% lithium carboxymethyl cellulose are evenly dispersed in deionized water using a double planetary mixer, and then evenly coated on a 5μm copper foil using an extrusion coating machine. After drying, rolling to a certain thickness and cutting to a certain width, the negative electrode sheet is obtained.

[0064] Step S2: Add the inorganic filler (nano-ceramic particles Al2O3) and dispersant (polyethylene glycol) to the organic solvent (dimethylformamide), and disperse them evenly to obtain the first slurry;

[0065] Step S3: Add the photocurable resin (bisphenol A diethylene glycol epoxy resin), electrolyte (LiPF6), binder (polyvinylidene fluoride), photoinitiator (diaryl iodine salt), and pore-forming agent (polyvinyl alcohol) to the first slurry and disperse them evenly to obtain the first electrolyte slurry;

[0066] Step S4: After coating the active material layer of the negative electrode sheet with the first electrolyte slurry using a scraper, let it stand and cure it under a 260nm mercury lamp, then heat it at 45℃ for 1 hour. The curing temperature is 25℃ and the time is 0.5 hours, thus obtaining the negative electrode sheet.

[0067] Preparation of positive electrode:

[0068] Step S1: 97.4% lithium nickel cobalt manganese oxide, 0.8% conductive carbon, 0.8% carbon nanotubes and 1.0% polyvinylidene fluoride are evenly dispersed in N-methylpyrrolidone using a double planetary mixer, and then evenly coated on 9μm aluminum foil on an extrusion coater. After drying and rolling, a positive electrode active material layer is obtained.

[0069] Step S2: Add the inorganic filler (nano-ceramic particles Al2O3) and dispersant (polyethylene glycol) to the organic solvent (dimethylformamide), and disperse them evenly to obtain the second slurry;

[0070] Step S3: Add the photocurable resin (bisphenol A diethylene glycol epoxy resin), electrolyte (LiPF6), binder (polyvinylidene fluoride), photoinitiator (diaryl iodine salt), and pore-forming agent (polyvinyl alcohol) to the first slurry, and disperse them evenly to obtain the second electrolyte slurry;

[0071] Step S4: After coating the active material layer of the positive electrode sheet with the second electrolyte slurry using a scraper, let it stand, heat it at 45°C for 1 hour, and then place it under a 260nm mercury lamp for curing. The curing time is 0.5 hours, thus obtaining the positive electrode sheet.

[0072] The electrolyte layer is fully covered on the electrode to replace the traditional diaphragm.

[0073] The first gel electrolyte membrane comprises the following raw materials in parts by weight: 8 parts photocurable resin, 6 parts electrolyte, 40 parts organic solvent, 5 parts negative electrode inorganic filler, 27 parts binder, 3 parts photoinitiator, 3 parts pore-forming agent, 3 parts dispersant, and the inorganic filler has a particle size of 500 nm; the second gel electrolyte membrane comprises the following raw materials in parts by weight: 8 parts photocurable resin, 6 parts electrolyte, 40 parts organic solvent, 15 parts positive electrode inorganic filler, 32 parts binder, 3 parts photoinitiator, 3 parts pore-forming agent, 3 parts dispersant, and the inorganic filler has a particle size of 500 nm.

[0074] The first gel electrolyte membrane has a thickness of 4 μm, the negative electrode plate has a thickness of 100 μm, and the negative electrode inorganic filler has a weight percentage of 5 parts; the second gel electrolyte membrane has a thickness of 6 μm, the positive electrode plate has a thickness of 80 μm, and the positive electrode inorganic filler has a weight percentage of 15 parts.

[0075] Battery manufacturing:

[0076] The positive and negative electrode sheets are stacked in sequence, with the electrolyte located between the positive and negative electrode sheets to provide safety isolation. The cells are wound to obtain a bare cell, which is then sealed with an aluminum-plastic film on the top and side. Electrolyte is injected and the cells are then encapsulated to obtain the secondary battery.

[0077] Example 2

[0078] Unlike Example 1, in this example, the inorganic filler for the negative electrode is ZrO2 nano-ceramic particles with a particle size of 600 nm, the thickness of the first gel electrolyte membrane is 3 μm, and the heating temperature is 60 °C.

[0079] The rest is the same as in Example 1, and will not be repeated here.

[0080] Example 3

[0081] Unlike Example 1, in this example, the inorganic filler for the negative electrode is La2O3 nano-ceramic particles with a particle size of 700 nm, the thickness of the first gel electrolyte membrane is 6 μm, and the heating temperature is 100 °C.

[0082] The rest is the same as in Example 1, and will not be repeated here.

[0083] Example 4

[0084] Unlike Example 1, the thickness of the second gel electrolyte membrane in this example is 5 μm.

[0085] The rest is the same as in Example 1, and will not be repeated here.

[0086] Example 5

[0087] Unlike Example 1, the thickness of the second gel electrolyte membrane in this embodiment is 8 μm.

[0088] The rest is the same as in Example 1, and will not be repeated here.

[0089] Example 6

[0090] Unlike Example 1, the weight of the positive electrode inorganic filler in this example is 17 parts.

[0091] The rest is the same as in Example 1, and will not be repeated here.

[0092] Example 7

[0093] Unlike Example 1, the weight of the positive electrode inorganic filler in this example is 20 parts.

[0094] The rest is the same as in Example 1, and will not be repeated here.

[0095] Comparative Example 1

[0096] Unlike Example 1, this comparative example uses a conventional diaphragm instead of the gel electrolyte membrane provided in this application.

[0097] The rest is the same as in Example 1, and will not be repeated here.

[0098] Comparative Example 2

[0099] Unlike Example 1, the thickness of the first gel electrolyte membrane in this comparative example is 10 μm.

[0100] The rest is the same as in Example 1, and will not be repeated here.

[0101] Comparative Example 3

[0102] Unlike Example 1, the second gel electrolyte membrane in this comparative example does not contain inorganic fillers.

[0103] The rest is the same as in Example 1, and will not be repeated here.

[0104] The lithium-ion batteries prepared in the examples and comparative examples were subjected to the following performance tests:

[0105] (1) Impedance test: The positive and negative electrode sheets coated with gel electrolyte membranes were cut into original sheets with a diameter of 16 mm, and assembled into a coin cell in the order of positive electrode shell-positive electrode sheet-gel electrolyte membrane-gel electrolyte membrane-negative electrode sheet-negative electrode shell, and electrolyte was added to wet the interface. The battery was connected to an electrochemical workstation for EIS test.

[0106] (2) Capacity retention test: The cell is clamped on the charge-discharge tester. The test conditions are constant current charge-discharge and voltage range of 2.0-4.5V. The assembled battery is pre-cycled for 3 cycles at a current density of 0.1C at room temperature, and then long-cycle charge-discharge test is performed at a current density of 1C. After the cell is cycled for 100 cycles, the discharge capacity of the first cycle and the discharge capacity of the 100th cycle are recorded.

[0107] The performance test results are shown in Table 1 below.

[0108] Table 1

[0109] Group Impedance test / Ω Capacity retention rate after 100 cycles / % Example 1 57 94 Example 2 63 91 Example 3 75 90 Example 4 59 92 Example 5 78 87 Example 6 75 86 Example 7 65 82 Comparative Example 1 88 82 Comparative Example 2 59 90 Comparative Example 3 79 65

[0110] As can be seen from the comparison of experimental data in Table 1 above, the gel electrolyte membrane provided in this application can replace conventional diaphragms while also having excellent high-pressure cycling performance.

[0111] A comparison of the test results from Example 1 and Comparative Example 1 shows that, compared to conventional separators, using a gel electrolyte membrane can enhance the adhesion between the electrolyte and the electrode, and reduce the gap between the electrode and the electrolyte during expansion. Especially at the corners of the battery cell, the gel polymer electrolyte can tightly adhere to the electrode interface at the corner, providing a lithium-ion transport channel, thereby reducing the risk of lithium plating at the corner.

[0112] Comparing the test results of Examples 1-5 and Comparative Example 2, it can be seen that when the thickness of the first gel electrolyte membrane is greater than the thickness of the second gel electrolyte membrane, the lithium ion transfer path between the positive and negative electrodes becomes larger, resulting in a deterioration in the cycle performance of the cell in the later stage.

[0113] A comparison of the test results from Examples 1, 6-7, and Comparative Example 3 reveals that when the gel electrolyte membrane does not contain inorganic fillers, lithium dendrites easily puncture the gel membrane layer during cycling, resulting in poor overall puncture resistance and a potential safety hazard. While increasing the weight percentage of inorganic fillers in the positive electrode can improve the oxidation resistance and mechanical strength of the second gel electrolyte to some extent due to their inherent properties, allowing it to maintain a high capacity retention rate even after 100 cycles at a 1C rate and a high cutoff voltage of 4.5V, the accumulation of inorganic fillers in the gel reduces the specific surface area, thus decreasing the cell's capacity retention rate.

[0114] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments described above, and any obvious improvements, substitutions, or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.

Claims

1. A secondary battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet and an electrolyte; the electrolyte is arranged between the positive electrode sheet and the negative electrode sheet, and the electrolyte includes a first gel electrolyte membrane and a second gel electrolyte membrane.

2. The secondary battery according to claim 1, characterized in that: The first gel electrolyte membrane is disposed on the negative electrode plate, and the second gel electrolyte membrane is disposed on the positive electrode plate.

3. The secondary battery according to claim 1, characterized in that: The second gel electrolyte membrane has a thickness greater than a thickness of the first gel electrolyte membrane.

4. The secondary battery according to claim 1, characterized in that: The thickness of the first gel electrolyte membrane is 3-6 μm, and the thickness of the second gel electrolyte membrane is 5-8 μm.

5. The secondary battery according to claim 1, characterized in that: The ratio of the thickness of the gel electrolyte membrane to the thickness of the electrode piece is 1:(10-50).

6. The secondary battery according to claim 1, characterized in that: The electrolyte comprises the following raw materials in parts by weight:

7. The secondary battery according to claim 6, characterized in that: The photocurable resin is at least one of bisphenol A diethylene glycol epoxy resin, triethylene glycol diamine diphenylmethane epoxy resin, isophorone diisocyanate, dimethylsiloxane and trimethylsiloxysilicate; And / or, the lithium salt is at least one of LiPF6, LiBOB, LiBF4, LiBOB, LiTFSI, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2.

8. The secondary battery according to claim 6, characterized in that: The organic solvent is at least one of dichloromethane, tetrahydrofuran, dimethylformamide and dimethyl sulfoxide; And / or, the inorganic filler is at least one of Al2O3, ZrO2, La2O3 and TiO2; And / or, the particle size of the inorganic filler is 50-900 nm.

9. The secondary battery according to claim 6, characterized in that: The polymer is at least one of polyvinylidene fluoride, polyacrylate, polyimide and polymethyl methacrylate; and / or, the photoinitiator is at least one of diaryliodonium salt, phenylxylene ketone, 1-hydroxycyclohexylphenyl ketone and dibenzoyl oxide; and / or, the pore former is a volatile organic compound and / or at least one of polyvinyl alcohol, polystyrene and polyurethane; And / or, the dispersant is at least one of sodium dodecyl sulfate, polyethylene glycol, polyacrylic acid and (3-aminopropyl)triethoxysilane.

10. A method for preparing a secondary battery according to claim 1, characterized in that: The following steps are involved: Step S1, adding the negative electrode inorganic filler and the dispersant into an organic solvent, and dispersing them uniformly to obtain a first slurry, and adding the positive electrode inorganic filler and the dispersant into an organic solvent, and dispersing them uniformly to obtain a second slurry; Step S2, adding a photocurable resin, an electrolyte, a binder, a photoinitiator and a pore-forming agent to a first slurry, and dispersing them uniformly to obtain a first electrolyte slurry, and adding a photocurable resin, an electrolyte, a binder, a photoinitiator and a pore-forming agent to a second slurry, and dispersing them uniformly to obtain a second electrolyte slurry; Step S3, coating the first electrolyte slurry and the second electrolyte slurry on the surface of the active material layer of the negative electrode sheet and the surface of the active material layer of the positive electrode sheet respectively, standing, heating at 45-75° C. for 0.5-2 h, and then curing under ultraviolet light for 0.1-1 h, thereby obtaining the positive electrode sheet and the negative electrode sheet; Step S4, stacking the positive electrode sheet and the negative electrode sheet in order, wherein the electrolyte is located between the positive electrode sheet and the negative electrode sheet to play a role of safety isolation, winding to obtain a bare battery cell, sealing the top and side with an aluminum-plastic film, injecting an electrolyte and packaging to obtain the secondary battery; Wherein, in step S1, the weight ratio of the negative electrode inorganic filler to the positive electrode inorganic filler is 1:(2-5).